A Jurisprudential Analysis of the Ammatoa Indigenous People's Legal Rights over the Management of Customary Forests in Bulukumba - Samad, Ansyaruddin; Rifdan, Rifdan; Dhahri, Irsyad (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
The Ammatoa Kajang indigenous community is a group that has lived for generations within the Kajang customary area, holding sovereignty over their land and natural resources, and regulating their socio-cultural life based on customary law and the traditional institution of